Is skilled immigration always good for growth in the receiving economy? - Leonid V. Azarnert (Bar-Ilan University, Department of Economics, 2010)
A highly skilled immigration can be growth enhancing if the positive contribution of the imported brains to the host economy's human capital stock outweighs the immigration-induced adverse effect on educational incentives for natives, or growth depleting if the latter effect dominates.
Keywords: F22; O15; O40; 330; skilled immigration; growth; Einwanderung; Hochqualifizierte Arbeitskräfte; Wirtschaftswachstum; Kleine offene Volkswirtschaft; Overlapping Generations; Theorie